Successful instrumentation and control systems design - Whitt, Michael D. (ISA, 2004)
Annotation This book describes the characteristics of a successful design package for a new instrumentation and control (I & C) system and delves into the business of design engineering. It explains the design process, the elements of a successful project, and specific issues to be addressed in a well-designed I & C system, and looks at the engineering products that enable practical design and maintenance. The book will be useful to maintenance, process, and mechanical engineers, designers, and design supervisors. Author information is not given. Annotation (c)2003 Book News, Inc., Portland, OR (booknews.com).
Keywords: Automatic control.; Engineering instruments.; elektronické knihy; electronic books